Evaluación de la eficacia de Trichoderma sp y Pseudomona sp para biorremediación de suelos contaminados con hidrocarburos - Muñoz Cuaical, Stalin David (2016)
The aim of this research was evaluate the power of bioremediation of the fungus Trichoderma sp and the bacteria Pseudomonas fluorescens in a sample of soil contaminated by hydrocarbons, in order to reduce the TPH (total polycyclic hydrocarbons) in soil. This project was completed in two phases: the field work consisted of soil sampling and the laboratory work consisted of installation of an assay with a DBCA system with 4 treatments (T0: control soil, T1: Soil + Trichoderma sp, T2: Soil + Pseudomonas fluorescens and T3 : Soil with Pseudomonas fluorescens + Trichoderma sp ) and 4 repetitions with controlled environmental conditions such as pH, temperature, electrical conductivity and moisture; the physico-chemical and TPH analyzes was performed at beginning and end of the assay for 3 months. The soil at beginning of the assay had macro and micro elements which are essential for microorganisms to degrade hydrocarbons. The initial TPH contamination in soil was 42070.3 mg / kg, and at the end of the assay the T1, T2 and T3 obtained an effective remediation, settling down within the permissible limits of RAOHE (environmental regulations hydrocarbon activities); demonstrating that all treatments work independently and in a consortium. The T3 (consortium) was the treatment that degraded more amount of hydrocarbons with a value of 379.2 mg / kg, the reason was because both microorganisms had the necessary mechanisms to degrade the hydrocarbon molecules, showing that bioremediation is an ecological and effective process for the degradation of hydrocarbons.